2015
DOI: 10.1080/21623945.2015.1049401
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenesis is under surveillance of Hsp90 and the high molecular weight Immunophilin FKBP51

Abstract: Adipose tissue plays a central role in the control of energy balance as well as in the maintenance of metabolic homeostasis. It was not until recently that the first evidences of the role of heat shock protein (Hsp) 90 and high molecular weight immunophilin FKBP51 have been described in the process of adipocyte differentiation. Recent reports describe their role in the regulation of PPARγ, a key transcription factor in the control of adipogenesis and the maintenance of the adipocyte phenotype. In addition, nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 146 publications
1
8
0
Order By: Relevance
“…Of these, HSP90, HSPA5/GRP78, and DNAJB1/HSP40 are involved in adipogenesis [8, 1517]. As an example, HSP90 regulates adipocyte differentiation by chaperoning PPARγ to control its stability, and HSP90 inhibition impedes the differentiation of 3T3-L1 preadipocytes and lipid accumulation [8, 18]. Moreover, HSPA5 is required for adipogenesis because when absent the differentiation of 3T3-L1 cells is impaired and mice demonstrate lipoatrophy [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, HSP90, HSPA5/GRP78, and DNAJB1/HSP40 are involved in adipogenesis [8, 1517]. As an example, HSP90 regulates adipocyte differentiation by chaperoning PPARγ to control its stability, and HSP90 inhibition impedes the differentiation of 3T3-L1 preadipocytes and lipid accumulation [8, 18]. Moreover, HSPA5 is required for adipogenesis because when absent the differentiation of 3T3-L1 cells is impaired and mice demonstrate lipoatrophy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins (HSPs) are an evolutionarily conserved superfamily of protein chaperones that exhibit diverse functions, such as the facilitation of protein folding, translocation, trafficking, and the targeted removal of aberrant proteins [13, 14]. Several HSPs, including HSP90, HSPA5 (GRP78), and DNAJB1 (HSP40), are involved in adipogenesis; for example, HSP90 promotes and DNAJB1 suppresses adipocyte differentiation [8, 1518]. Heat shock protein A12A (HSPA12A), which was cloned from mouse atherosclerotic lesions in 2003, is a novel and distinct member of the mammalian heat shock protein 70 (HSP70/HSPA) family due to it containing an atypical Hsp70 ATPase domain [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent data suggests that FKBP51 is one of the most highly induced proteins during WAT adipocyte differentiation [72], [103]. In vitro studies in 3T3-L1 pre-adipocytes have shown that FKBP51 is an important regulator of adipocyte maturation [104]. In fact, loss of FKBP51 in pre-adipocytes prevents adipocyte differentiation and accumulation of lipid droplets [101].…”
Section: Molecular Regulation Of Metabolic Pathways By Fkbp51mentioning
confidence: 99%
“…So far, there are no conclusive data on a function of FKBP51 in modulating MR, AR, or PR function in adipocytes. Interestingly, especially adipocyte GRs are activated by glucocorticoids and are associated with adipogenesis [107] (the interplay between FKBP51, Hsp90 and GR are reviewed in detail elsewhere [64], [104]). Within the first hours of adipocyte differentiation, FKBP51 rapidly translocates from the mitochondria to the nucleus.…”
Section: Molecular Regulation Of Metabolic Pathways By Fkbp51mentioning
confidence: 99%
“…97 In support of this, we have recently reported that the high molecular weight immunophilin (IMM) FKBP51, a member of the glucocorticoid receptor (GR)Hsp90Hsp70p23 heterocomplex required for proper signaling of steroid nuclear receptors, 74 translocates from mitochondria to the nucleus at the onset of adipogenesis. 98,99 In the nucleus, FKBP51 not only co-localizes with lamin B in the fragmented pattern of the lamina (Fig. 1B), but also interacts with lamin B.…”
Section: The Nuclear Lamina Is Reorganized At the Onset Of Adipogenesismentioning
confidence: 99%